282 The Influence of RFI classification and cow age on body weight and body condition change, supplement intake and grazing behavior of beef cattle winter grazing mixed-grass rangelands. (30th November 2020) - Parsons, Cory T; Dafoe, Julia M; Wyffels, Samuel; Van Emon, Megan; DelCurto, Timothy; Boss, Darrin L
Abstract: behavior of beef cattle winter grazing rangelands in North Central Montana. A herd of non-lactating commercial Angus cows, n = 205 (yr-1) and n = 203 (yr-2), ranging in age from 1 to 9 yr old, grazed rangeland pastures (586 ha) from mid-October to early January of 2018 and 2019. Cows were grouped into 6 age classes to evaluate the effects of RFI and age on average daily individual supplement intake, CV of supplement intake, and intake rate, as well as changes in body weight and body condition during an 84-day grazing period each year. Additionally, 30 cows were stratified by age and RFI and fitted with Lotek GPS collars each year to record distance traveled and time spent grazing. Change in cow weight differed by year where cows in yr-1 gained 26.3 ± 1.96 kg while cows in yr-2 lost 19.2 ± 1.96 kg during the 84-day grazing period (P < 0.01). Change in BCS exhibited an age × RFI interaction (P = 0.05); however, an analysis within age groups did not result in differences between RFI classifications (P ≥ 0.27). There was an interaction between RFI, age and year related to supplement intake expressed as g∙kg cow bw -1 ∙d -1 where in year 2, 4-yr-old high RFI cattle consumed less supplement than 4-yr-old low and average RFI cattle (P < 0.01). Supplement intake rate expressed as g∙min -1 also differed by year (P < 0.01), with cows in yr-1 consuming less supplement per minute than in yr-2 (29.9 ± 1.81 and 91.8 ± 1.87). There were no effects of RFI, cow age or year on time spent grazing (P ≥ 0.19) with cows averaging 6.1 ± 0.61 hrs per day grazing. In summary, cow age had an influence on supplement intake, change in weight and body condition, and grazing behavior, while RFI classification had minimal effects.